1977
DOI: 10.7901/2169-3358-1977-1-633
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Naphthalenes Within Exposed Fundulus Similus and Correlations With Stress Behavior

Abstract: Fundulus similus was exposed to naphthalene via oral administration, and naphthalene plus alkylnaphthalenes in water. The distribution of these compounds within the organs and tissues of the fish was monitored with time. Turn-over times for these compounds were relatively rapid, particularly in the case of naphthalene administered orally. Accumulation within detoxification (liver) and storage (gall bladder) was expected, but accumulation and retention in the brain were higher than anticipated. Stress-produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The progression of abnormal behavior during the preexposure period, from normal t o disoriented a n d eventually unconscious, is consistent with oil-induced anesthesia [27] Similar behavioral effects were reported by Morrow [28] and Dixit and Anderson [29] The relation between behavior a n d lethality was not directly addressed in this study However, even severe behavioral changes such as loss of equilibrium or immobility d o not necessarily imply death, because no mortalities of preexposed adults were observed in the control tanks during the toxicity test, even though 45% of the fish in the lOO-mg/L No 2 fuel oil (2FO) preexposure tank either displayed loss of equilibrium or were lying o n the bottom of the tank o n the day they were transferred to the toxicity test control tank Assuming that alterations in behavior were related t o the biochemical status of the fish, the ability of behaviorally altered fish t o recover suggests that the effects of preexposure are reversible This hypothesis is supported by biochemical analyses [ I 11 in which a gradual return of several biochemical parameters was observed over a 14-d period in oil-free water Sensitization due t o preexposure was also observed in separate laboratory studies with phenol a n d refinery wastewater a n d in a refinery field study [16] Sensitization may thus be a generalized response of rainbow trout exposed to organic compounds Our method of establishing preexposure levels was based o n a biological response and not on a n arbitrarily selected number Similar relative exposure levels have resulted in acclimation t o many toxicants [ 16-1 81 Consequently, sensitization may be a real a n d potentially important phenomenon stemming from preexposure t o certain organic chemicals…”
Section: B L Steadmanetalsupporting
confidence: 76%
“…The progression of abnormal behavior during the preexposure period, from normal t o disoriented a n d eventually unconscious, is consistent with oil-induced anesthesia [27] Similar behavioral effects were reported by Morrow [28] and Dixit and Anderson [29] The relation between behavior a n d lethality was not directly addressed in this study However, even severe behavioral changes such as loss of equilibrium or immobility d o not necessarily imply death, because no mortalities of preexposed adults were observed in the control tanks during the toxicity test, even though 45% of the fish in the lOO-mg/L No 2 fuel oil (2FO) preexposure tank either displayed loss of equilibrium or were lying o n the bottom of the tank o n the day they were transferred to the toxicity test control tank Assuming that alterations in behavior were related t o the biochemical status of the fish, the ability of behaviorally altered fish t o recover suggests that the effects of preexposure are reversible This hypothesis is supported by biochemical analyses [ I 11 in which a gradual return of several biochemical parameters was observed over a 14-d period in oil-free water Sensitization due t o preexposure was also observed in separate laboratory studies with phenol a n d refinery wastewater a n d in a refinery field study [16] Sensitization may thus be a generalized response of rainbow trout exposed to organic compounds Our method of establishing preexposure levels was based o n a biological response and not on a n arbitrarily selected number Similar relative exposure levels have resulted in acclimation t o many toxicants [ 16-1 81 Consequently, sensitization may be a real a n d potentially important phenomenon stemming from preexposure t o certain organic chemicals…”
Section: B L Steadmanetalsupporting
confidence: 76%
“…Accumulation of naphthalenes in organs of Fundulus similus exposed to WSF of No. 2 fuel oil has been documented by Dixit and Anderson ( 1977). Concentrations of total naphthalenes in excess of 200 ppm in the brain were found to correlate with loss of locomotor and regulatory capabilities.…”
Section: Biological Effectsmentioning
confidence: 99%
“…Further, Payne et al [22] noted in laboratory studies with flounder that the accumulation of metabolites in bile approached the sensitivity of the induction of mixed-function-oxygenase enzymes for assess- suggests that metabolites of the relatively soluble low-molecular-weight PAH component of fuel oil, which may occur in water at relatively low levels for only a few days, could also accumulate in the bile of fish to a sufficient degree to be readily detected by fluorescence. The fish in this study were injected with a relatively high level of hydrocarbons but it should be noted that total naphthalenes have been shown to bioaccumulate in gall bladder bile by a factor of 1,000 or more in fish exposed to water-soluble fractions of fuel oil for a few days [23]. In other words, even exposure to water-soluble levels of hydrocarbons in the low pg/g range could produce metabolite levels in bile detectable by simple fluorimetric procedures; fluorescence can later be supplemented with MS or, as this study demonstrated, with 'H-NMR spectroscopy for more definitive "proof" of hydrocarbon contamination.…”
Section: Resultsmentioning
confidence: 99%